2012
DOI: 10.4321/s1130-01082012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to survival in hepatocellular carcinoma in the geographic area of Sabadell (Catalonia, Spain)

Abstract: BAckground: hepatocellular carcinoma (HCC) is a very frequent tumor. Screening for the disease is effective, but the prognostic factors are difficult to evaluate.Objectives: 1. To determine epidemiological data and the clinical course of HCC in our setting. 2. To compare patient survival according to whether screening is performed or not. 3. To evaluate survival prognostic factors.Patients and methods: data on the epidemiology and clinical course of patients diagnosed with HCC were collected on a prospective b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Rates of early tumor detection were consistent across study location (OR 2.22 [95% CI 1.75–2.81] among studies conducted in Asia [17],[34],[38],[49] versus 2.00 [95% CI 1.70–2.35] among studies in Europe [37],[42],[55],[57],[63] versus 2.31 [95% CI 1.79–2.99] among studies in the United States [32],[33],[35],[41],[43],[44],[45],[47],[52],[53],[61]), study period (OR 2.22 [95% CI 1.77–2.79] among studies assessing surveillance in the 1990s [17],[29],[49],[53],[55] versus 2.18 [95% CI 1.86–2.56] among studies assessing surveillance after 2000 [18],[32][35],[37],[38],[41][43],[45],[47],[52],[57],[61],[63]), and type of surveillance tests (OR 2.04 [95% CI 1.55–2.68] with ultrasound alone [18],[32],[38],[47],[61] versus 2.16 [95% CI 1.80–2.60] with ultrasound and/or AFP [17],[29],[34],[35],[37],[42][45],[49],[52],[53],[55],[63]). There was no significant difference in the association between HCC surveillance and early stage tumor detection by study design ( p  = 0.10), with patients detected by surveillance being more likely to be found at an early stage in both subgroups.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…Rates of early tumor detection were consistent across study location (OR 2.22 [95% CI 1.75–2.81] among studies conducted in Asia [17],[34],[38],[49] versus 2.00 [95% CI 1.70–2.35] among studies in Europe [37],[42],[55],[57],[63] versus 2.31 [95% CI 1.79–2.99] among studies in the United States [32],[33],[35],[41],[43],[44],[45],[47],[52],[53],[61]), study period (OR 2.22 [95% CI 1.77–2.79] among studies assessing surveillance in the 1990s [17],[29],[49],[53],[55] versus 2.18 [95% CI 1.86–2.56] among studies assessing surveillance after 2000 [18],[32][35],[37],[38],[41][43],[45],[47],[52],[57],[61],[63]), and type of surveillance tests (OR 2.04 [95% CI 1.55–2.68] with ultrasound alone [18],[32],[38],[47],[61] versus 2.16 [95% CI 1.80–2.60] with ultrasound and/or AFP [17],[29],[34],[35],[37],[42][45],[49],[52],[53],[55],[63]). There was no significant difference in the association between HCC surveillance and early stage tumor detection by study design ( p  = 0.10), with patients detected by surveillance being more likely to be found at an early stage in both subgroups.…”
Section: Resultsmentioning
confidence: 70%
“…Among the 16 cohort studies that reported both early detection (using Milan or BCLC criteria) and curative treatment rates [17],[29],[32][35],[37],[38],[43],[44],[47],[49],[53],[55],[61],[63], we found a moderately strong positive correlation between early detection rates and curative treatment rates between studies (Pearson's correlation r = 0.54) (Figure S4). This finding suggests the association between surveillance and receipt of curative treatment is mediated by improved early tumor detection rates.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations